Endobronchial lipoma: a rare cause of subsegmental bronchial obstruction - Pavel V. Pavlov (Respirology Case Reports, 2020)
Endobronchial lipoma is a rare cause of bronchial obstruction. Early identification and diagnosis of endobronchial lipoma can prevent damage of the lung parenchyma. Clinicians should be aware of this rare tumour. Bronchoscopic resection is the first choice of treatment, but surgical operation should be indicated in certain circumstances.